(untitled) (Italian Journal of Public Health, 2003)
Health Technology Assessment (HTA) has been defined in different ways, nevertheless it can be described briefly as a multidisciplinary process of analysis dealing with evidence and context to inform decision making in health care. For decades HTA and related fields, aimed to produce and encourage the use of scientific evidence to inform decision making, at all levels of the health care system, from policy making and management to clinical decision making [1,2]. Scientific evidence involved in the HTA process may refer to efficacy, effectiveness, safety, needs, appropriateness, efficiency, equity, acceptability and some other issues related to the effect of the introduction, use and diffusion of medical technologies on health and health care. The evaluation, with formal rules, of the quality of a vailable scientific information is an important step of the HTA process as are the skills required for literature searching. The source of scientific information should not be limited to clinical literature, but also exploit other areas of knowledge such as epidemiology, social sciences,economics,health services research among others [1].The best method to be used in the HTA analysis process obviously depends on the uncertainties to be assessed. It could range from the synthesis and/or integration of scientific information to production of primary data.The latter is the option of choice when there is insufficient existing evidence or its quality is poor. The assessments often require a multidisciplinary and multi-method approach, the former, of course,must be chosen after translating the uncertainty into sound research questions.